Dialektika antara Kemaslahatan dan Teks dalam Syariah - Arifin, Moch. Zainul (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article discusses the dialetics between the benefit and the text in shariâah. The purpose of shariâah is to reach the benefit of mankind. It means that the entire texts and their laws serve to realize the benefit and to prevent damage, and should be based on the principle of beneficial understanding, the application of which within the scope of the benefit, and the text as a standard of benefit. The benefit is an important spirit behind shariâah. Because of that, the understanding of the text in a legal reasoning process needs a solid foundation. Basically, the emergence of contradiction between benefit and text is nothing other than the two things: first, errors in understanding and concluding the benefit; second, errors in understanding and actualizing the text. Actualization of the benefit of the text is a branch and an expansion of the welfare interpretation of the text. This actualization plays an important role in eliminating the contradiction between the text and welfare. Therefore, it is necessary to actualize the enlightened benefit by seeing, considering, and excluding the conditions that lead to a damage.Keywords: Benefit, text, shariâah